Pengembangan Bisnis Insting Coffee Agus Sutardi - Agus Sutardi; Ayu Wandira; Noval Robani Hardiansyah; Salsabilla Puspa Rianty; Sawitri Nurhayati; Winda Asiah (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine whether or not Coffe's Instinct business is feasible to run based on its business feasibility study. Descriptive qualitative research method is the method used in this study. The object of this study is the Instinct Coffee business located on Jl. Bojong No.98, Soreang, Bandung Regency. The result of this research is that the Coffee Instinct business is feasible to run with several points of improvement for business development.